ANALYSIS OF GENOTYPIC AND PHENOTYPIC CORRELATIONS AND PATH COEFFICIENTS IN 40 GENOTYPES OF RAIN-FED UPLAND RICE (Oryza sativa L.) IN OYO AND OGUN STATES REGIONS OF NIGERIA - ABEGUNDE, Isaac (Journal of Agricultural Sciences (Belgrade), 2024)
The research delved into the genetic correlations among agronomic traits within a diverse rice germplasm comprising 40 accessions, scrutinized across varied locations and cropping seasons. The correlation analysis unearthed compelling associations among multiple plant characteristics. The genotypic correlation shed light on connections involving culm length, panicle length, plant height, leaf dimensions, effective tillering, and yield. Meanwhile, the phenotypic correlation underlined a robust linkage between yield, panicle numbers, days to maturity, and days to flowering. Moreover, it unveiled intricate interrelationships among traits like grain length, width, and leaf dimensions. These findings were consistently reinforced by data obtained across different locations and years, confirming the pivotal role these traits play in determining yield and overall plant attributes across diverse genotypes. Essentially, this study underscores the pivotal role of specific agronomic traits in influencing yield. Enhancing these traits could lead to improved yields, as evidenced by their indirect relationships. Consequently, it strongly advocates for further comprehensive research to unravel the genome-wide connections between these traits and yield, providing crucial insights into optimizing crop productivity.